Development of an Arduino-Based Truck Load Detection System for Bridge Safety Monitoring - Delima Astuti Rambe; Dwi Anggita Ramanda; Husna Juli Gulvira; Muhammad Ilham Siregar; Meiliyani Br Ginting; Ita Margaretta Br Tarigan (Karya Techno Solusindo, 2026)
The safety of bridge structures is very important to consider, especially in withstanding the weight of passing trucks. Overloading can cause structural damage that can potentially jeopardize the safety of bridge users. Therefore, a truck load weight detection system is needed that is able to monitor the load in real-time and provide early warning in the event of overloading. This research aims to design and implement an Arduino-based truck load weight detection system installed on the bridge. This system uses a load sensor (load cell) to measure the weight of passing vehicles, where the weight data is then processed by an Arduino arduiuno. The system is equipped with a wireless communication module that allows weight data to be sent directly to the control center or bridge operator. The results of system testing show that this system is able to detect the weight of truck loads with a good level of accuracy. With this system, it is expected to improve bridge safety and provide accurate information related to the distribution of loads passing over the bridge. REFERENCES Arsyad, O. R., & Kartika, K. P. (2021). Design and build safe safety devices using Arduino-based fingerprint sensors. JATI (Student Journal of Informatics Engineering), 5(1), 1–6. Gunawan, G., & Ardiyansyah, M. R. (2023). Design and build an Arduino-based photovoltaic panel performance tester. State Polytechnic at the End of the Line. Handiko, Y. T. (2022). Design and Build a Digital Scale Model Using Load Cell Sensors and IoT-Based Scale Recording. Kartika Riyanti, K. P., Kakaravada, I., & Ahmed, A. A. (2022). An Automatic Load Detector Design to Determine the Strength of Pedestrian Bridges Using Load Cell Sensor Based on Arduino. Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 4(1), 15–22. https://doi.org/10.35882/ijeeemi.v4i1.3 Kazuya, A. S., Ariyadi, T., Dasmen, R. N., & Fitriani, E. (2024). Design of Digital-Based Scales Equipped with Metal Detectors as Metal Sensors. Journal of Tambusai Education, 8(1), 14261–14277. Khristianto, W. & et al. (2022). Management Information System: The purpose of the Management Information System. In CV. Pena Persada (April Issue). Kurnia, R., Firdaus, R., Lufti, L., & Anshor, M. H. (2019). Load cell sensor automation to overcome vehicle overload. National Journal of Electrical Engineering, 8(2), 81. https://doi.org/10.25077/jnte.v8n2.666.2019 Laili, D. T., & Bahri, S. (2022). Prototype of Car Parking System Using Load Cell Sensor with Android-Based Arduino Mega 2560. Coding Journal of Computers and Applications, 8(1). Nurlaila, N., Paembonan, S., & Suppa, R. (2024). Design Arduino-based vehicle speed detection. Journal of Informatics and Applied Electrical Engineering, 12(3). Pranita, E. (2023). Automatic bridge control uses Arduino-based ultrasonic sensors. ICTEE Journal, 4(2), 13. https://doi.org/10.33365/jictee.v4i2.3143 Rachmawati, P. (n.d.). Digital Scale Simulation Design Using HX711 Sensor with Additional ESP32-Based Buzzer. Ridwan, M., Widiastiwi, Y., Zaidiah, A., Purabaya, R. H., Isnainiyah, I. N., Ardilla, Y., & Rahayu, T. (2021). Management Information Systems. Widina Publisher. Rizal-Alfariski, M., Dhandi, M., & Kiswantono, A. (2022). Automatic Transfer Switch (ATS) Using Arduino Uno, IoT-Based Relay and Monitoring. Journal of Telecommunication Systems, Electronics, Control Systems, Power Systems and Computers, 2(1), 1–8. Rustandi, A. (2020). Monitoring Current and Electrical Power with Notification System from Smartphones in Internet of Things (IoT)-Based Household Electrical Installations. Indonesian Computer University. Sibuea, S., & Saftaji, B. (2020). The design of the vehicle load monitoring system uses load cell sensor technology. Journal of Informatics and Computer Technology, 6(2), 144–156. https://doi.org/10.37012/jtik.v6i2.309 Simanjuntak, R. S. (2023). Design and build